Introduction to 3+1 numerical relativity - Alcubierre, Miguel (Oxford : Oxford University Press, 2008)
Starting from basic general relativity, this book introduces all the concepts and tools necessary for the fully relativistic simulation of astrophysical systems with strong and dynamical gravitational fields.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Relativity (Physics); Space and time -- Mathematics